Effectiveness of personalized smoking cessation intervention based on ecological momentary assessment for smokers who prefer unaided quitting: protocol for a randomized controlled trial - Zhang, Min Jin; He, Wan Jia Aaron; Luk, Tzu Tsun; Wang, Man Ping; Chan, Sophia Siu Chee; Cheung, Yee Tak Derek (Frontiers in Public Health, 2023)
Ecological momentary assessment (EMA)-based smoking cessation intervention may help personalize intervention for smokers who prefer to quit smoking unaided. This study aims to evaluate the effectiveness of EMA-based phone counseling and instant messaging for smoking cessation.This is a two-arm, accessor-blinded, simple individual randomized controlled trial (allocation ratio 1:1). Participants will be recruited from community sites and online platforms in Hong Kong. Interventions will be delivered via a phone call and instant messaging. Current adult smokers who (1) self-report no intention to use smoking cessation services and medication in the coming month and (2) have not used smoking cessation services or nicotine replacement therapy in the past 7 days will be recruited.Recruited participants will be randomized to intervention or control groups by an online randomizer. All participants will be required to complete EMAs (5 times per day for 7 consecutive days). The intervention group (n=220) will receive a nurse-led brief phone counseling immediately after the 1-week EMAs and 10-week EMA-based advice via instant messaging applications (e.g., WhatsApp, WeChat). The 10-week EMA-based advice covers a summary of the 1-week EMAs, and tailored cessation support focused on personalized smoking triggers. The control group (n=220) will not receive any intervention during the same period. The primary outcomes are participants' progression toward smoking cessation assessed by the Incremental Behavior Change towards Smoking cessation (IBC-S) and biochemically validated abstinence at 3-month follow-up. Secondary outcomes include self-reported and biochemically validated tobacco abstinence at 6-month follow-up.The findings will provide evidence that the EMA-based tailored smoking cessation intervention can be adapted as a new health promotion strategy for current smokers who